Update on the Protein Homeostasis Network in Bacillus subtilis - Matavacas, Judith; von Wachenfeldt, Claes (Frontiers in Microbiology, 2022)
Protein homeostasis is fundamental to cell function and survival. It relies on an interconnected network of processes involving protein synthesis, folding, post-translational modification and degradation as well as regulators of these processes. Here we provide an update on the roles, regulation and subcellular localization of the protein homeostasis machinery in the Gram-positive model organism Bacillus subtilis. We discuss emerging ideas and current research gaps in the field that, if tackled, increase our understanding of how Gram-positive bacteria, including several human pathogens, maintain protein homeostasis and cope with stressful conditions that challenge their survival.